The application of the SMETA audit protocol on the management of the CSR of Peruvian companies : a case study of standardization via SMETA in manufacturing companies - Medina Rodriguez, Alicia (2016)
Standardization in Corporate Social Responsibility has become more popular since re-cent years. A wide range of standards that seek to implement and evaluate the Corpo-rate Social Responsibility in companies, has become increasingly popular worldwide nowadays especially when companies producing goods and services are required by their international customers worldwide to obtain these standards. Most studies of this phenomenon have been done from the point of view of big companies and international brands and does not take into account the point of view of manufacturers located in the developing countries, were most goods are manufactured. This thesis investigates the influence of the Corporate Social Responsibility standardization through the SMETA audit protocol on the Corporate Social Responsibility performance of five different Pe-ruvian manufacturing companies. In order to gain a wide insight on how the application of the SMETA is helping the Corporate Social Responsibility performance on these companies, qualitative interviews to companies’ representatives and five Corporate So-cial Responsibility auditors with expertise auditing the SMETA standard, were per-formed. Additionally the five companies’ SMETA initial audit reports were also ana-lysed as secondary data for this research. The most important benefits, drawbacks and challenges that these companies encountered when implementing the standard, were detected. The findings after analysing the data obtained from the interviews indicated that one of the main drivers for companies to adopt the Corporate Social Responsibility standards such as the SMETA, come from the requirements and demands of international clients and big companies. Before the appearance of these clients’ demands, the only Corporate Social Responsibility measures or initiatives practiced by these companies were closely related to mere philanthropy in most cases. Only one company was found to have a strategic long-term views of developing Corporate Social Responsibility in its organiza-tion. Other findings encountered suggest that the SMETA standard has impacted posi-tively to the Corporate Social Responsibility performance of these companies. Auditors also expressed that Corporate Social Responsibility in the country’s companies has been started and fostered mostly due to the implementation of standards such SMETA as a requirement from international clients. In addition, this thesis also discusses some limi-tations in the studies that can suggest future lines of research.